Postload Plasma Glucose but Not Fasting Plasma Glucose Had a Greater Predictive Value for Cardiovascular Disease in a Large Prospective Cohort Study in Southwest China - Wang, Yingying; Yu, Lisha; Wang, Yiying; Zhou, Jie; Wu, Yanli; Liu, Tao; Wang, Na; Fu, Chaowei (Frontiers in Cardiovascular Medicine, 2022)
Background Uncertainty remains regarding the relevance of glycemia, though below the threshold for diabetes, for the risk of cardiovascular disease (CVD) among the Southwest Chinese. We aimed to examine the associations of the first-onset CVD with fasting plasma glucose (FPG) and 2-h postload glucose (2h-PG) in Southwest China. Methods The current study examined data from the Guizhou Population Health Cohort Study (GPHCS) of 9280 participants aged 18 to 95 years recruited from 12 areas since 2010 in Guizhou Province, Southwest China. Participants were followed-up until December, 2020. Primary outcomes were the first onset of a composite of or one of major CVD events, including ischaemic stroke, haemorrhagic stroke and myocardial infarction. FPG, 2h-PG, other metabolic factors and some demographic factors were collected at baseline. Cox proportional hazards models were used to estimate the risk of CVD associated with FPG and 2h-PG. Stratified analysis were conducted among participants across different modifiable risk factors and demographic features Results During a median of 6.58 years of follow-up, of 7593 participants with available data for analysis, 174 experienced at least one CVD events, 158 developed stroke (including 126 ischemic stroke and 39 Ischemic stroke events), and 24 developed myocardial infarction. The risk of major CVD events was significantly increased with elevated 2h-PG but not FPG. Compared with participants in the lowest tertile of 2h-PG, those in the highest tertile had a 1.87-fold (95%CI: 1.26-2.77) increased risk for overall CVD, a 1.82-fold (95%CI: 1.20-2.75) increased risk for overall Stroke, and a 1.82-fold (95%CI: 1.20-2.75) increased risk for ischemic stroke, respectively, after adjustment for age, sex, smoking, ethnic group, education level, systolic blood pressure (SBP), triglycerides (TG), body mass index (BMI) and waist circumference (WC). However, there was no relation of glycemia of haemorrhagic stroke or myocardial infarction (P>0.05). The effect sizes in the associations of CVD with 2h-PG become enhanced among those within normal range of glycemia, SBP, TG, BMI. Conclusions 2h-PG, in contrast to FPG, is a significant indicator in predication of CVD in Southwest Chinese. Elevated 2h-PG, though below the below the threshold for diabetes, remains independently increased the risk of CVD.